Vascular endothelial growth factor-A165b prevents diabetic neuropathic pain and sensory neuronal degeneration - Hulse, Richard P.; Beazley-Long, Nicholas; Ved, Nikita; Bestall, Samuel M.; Riaz, Hamza; Singhal, Priya; Ballmer Hofer, Kurt; Harper, Steve J.; Bates, David O.; Donaldson, Lucy F. (Portland Press, 2015)
Diabetic peripheral neuropathy affects up to half of diabetic patients. This neuronal damage leads to sensory disturbances, including allodynia and hyperalgesia. Many growth factors have been suggested as useful treatments for prevention of neurodegeneration, including the vascular endothelial growth factor (VEGF) family. VEGF-A is generated as two alternative splice variant families. The most widely studied isoform, VEGF-A165a is both pro-angiogenic and neuroprotective, but pro-nociceptive and increases vascular permeability in animal models. Streptozotocin (STZ)-induced diabetic rats develop both hyperglycaemia and many of the resulting diabetic complications seen in patients, including peripheral neuropathy. In the present study, we show that the anti-angiogenic VEGF-A splice variant, VEGF-A165b, is also a potential therapeutic for diabetic neuropathy. Seven weeks of VEGF-A165b treatment in diabetic rats reversed enhanced pain behaviour in multiple behavioural paradigms and was neuroprotective, reducing hyperglycaemia-induced activated caspase 3 (AC3) levels in sensory neuronal subsets, epidermal sensory nerve fibre loss and aberrant sciatic nerve morphology. Furthermore, VEGF-A165b inhibited a STZ-induced increase in Evans Blue extravasation in dorsal root ganglia (DRG), saphenous nerve and plantar skin of the hind paw. Increased transient receptor potential ankyrin 1 (TRPA1) channel activity is associated with the onset of diabetic neuropathy. VEGF-A165b also prevented hyperglycaemia-enhanced TRPA1 activity in an in vitro sensory neuronal cell line indicating a novel direct neuronal mechanism that could underlie the anti-nociceptive effect observed in vivo. These results demonstrate that in a model of Type I diabetes VEGF-A165b attenuates altered pain behaviour and prevents neuronal stress, possibly through an effect on TRPA1 activity.